THE RELATION BETWEEN EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL EFFECTIVENESS AT PT. TASPEN (PERSERO) MANADO - Sumaraw, Josefina M.; Worang, Frederik G.; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2018)
Abstract: An engaged employee is aware of organization objectives and works more effort to improve performance within the job for the benefit of the organization. Employee engagement develops positive attitude among the employees towards the organization. Proper attention on engagement strategies will increase the organizational effectiveness in terms of higher productivity, profits, quality, customer satisfaction, and employee retention. This study is to investigate the relationship between employee engagement and organizational effectiveness using qualitative approach and convenience sampling method that conducted interviews to ten informant at PT. Taspen. The finding proves that there is a meaningful relationship between the level of employee engagement and organizational effectiveness. The data analysis shows that performance of employee engagement effected by career development, compensation and benefits, organizational culture and policies and work environment. The recommendations are Â the company should know the level of their employee engagement, and more focus on human resources program such as job design, development opportunities, fair treatment, gave better work environment to motivate employees with high engagement level. The better the reward and recognition in the company the better the employee engagement.Â Keywords: employee engagement, organizational effectiveness.